High School Students’ Perceptions of Wattpad-Based Extensive Reading for Reading Skill Development - Nurhanifah Qurroti A'yunin (Retain: Journal of Research in English Language Teaching, 2025)
This study investigates how high school students feel about reading extensively from digital books, especially Wattpad, and the advantages they see in terms of their reading abilities. Because they gave them more freedom to select engaging material and reduced the sense that reading was a chore, students usually regarded digital novels to be entertaining, approachable, and inspiring. In terms of the advantages, students stated that reading on digital platforms enhanced their comprehension of English literature, increased their vocabulary, and improved their reading fluency. Based on their active participation in the English Conversation Club (ECC) at one of public high school in Gresik, 38 students were chosen as participants. A Likert-scale questionnaire was used in this study's descriptive quantitative methodology to collect data. According to the findings, students not only had a favorable opinion of extensive reading on Wattpad but also saw a discernible improvement in their reading skills, indicating that digital extensive reading can be both entertaining and useful in EFL settings.